Applied Mathematics to Mechanisms and Machines - Rubio Alonso, Higinio; Caballero, Alejandro; Meneses Alonso, Jesus; Soriano-Heras, Enrique (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book brings together all 16 articles published in the Special Issue "Applied Mathematics to Mechanisms and Machines" of the MDPI Mathematics journal, in the section "Engineering Mathematics". The subject matter covered by these works is varied, but they all have mechanisms as the object of study and mathematics as the basis of the methodology used. In fact, the synthesis, design and optimization of mechanisms, robotics, automotives, maintenance 4.0, machine vibrations, control, biomechanics and medical devices are among the topics covered in this book. This volume may be of interest to all who work in the field of mechanism and machine science and we hope that it will contribute to the development of both mechanical engineering and applied mathematics.